Air quality assessment in Perlis - Nurul Faizliyana Kamil (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
The objectives of this study are ; to compare the behaviour of the air pollutants and meteorological variables for day time and night time ; to determine the main factor that affect air pollution in Perlis ; to develop the multiple linear regression model on the O3 concentration based on the air pollutant and meteorological variables for day time and night time.